An Analysis upon Some Accounting Practices of SME: A Review: Exploring Accounting Practices and Management Accounting in SMEs (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The study revealed that the majority of the studied firm has no formal accounting practice. The study also revealed that the major sources of finance available for the establishment and expansion of SMEs are personal saving, microfinance, money from friends or relative, iqub and less from banks. The result of ordinary least square regression evidences thatvariables such as capital, manager education level and age of the firms are the significant determinants of firms’ accounting practices whereas the problems significantly associated with access to bank credits are the demand for collateral, accounting practice or formal accounting information and age of the firm.There have been the recent calls for additional research in order to enhance the understanding of the adoption of management accounting practices (MAPs) in small and medium sized enterprises (SMEs). This, allied to an increasing importance of SMEs around the world especially in developing countries, is the motivation for this research. This research explores the uptake of a broad range of MAPs in SMEs identifies the roles of MAPs in the management of SMEs determines factors that affect the extent of use of MAPs in SMEs and lastly examines the relationship between the use of MAPs and organizational performance of SMEs.